Application of solitaire double-stent thrombectomy in the treatment of accessory middle cerebral artery occlusion: a case report - Han, Qi; Dong, Guang-Hui; Zhu, En-Bo; Lin, Ming-Quan; Liu, Guang-Lin; Jin, Guang-lin; Qu, Lin-Zhuo; Guan, Hong-Jian; Che, Hui-ying (Frontiers in Surgery, 2025)
The accessory middle cerebral artery (AMCA) refers to the cerebral vascular variation originating from the anterior cerebral artery, passing through the lateral fissure and accompanying the middle cerebral artery (MCA), and participating in the blood supply area of the MCA. Relevant literature reports that the incidence of this variant vessel is 0.3%–2.7% (autopsy) and 0.26%–4.0% (cerebral angiography), respectively. This article reports a case of acute MCA occlusion with AMCA mutation. The occluded main MCA was successfully opened using a Solitaire double-stent thrombectomy to avoid mistaking AMCA for the main MCA.